The Transaction E-Commerce in Islamic/Sharia Law - Lathifah Hanim (Jurnal Akta, 2022)
This research aims to know e-commerce systems, sellers and buyers do not meet in person, but meet in cyberspace with the goods to be transacted usually displayed in the catalog. This kind of transaction is actually quite profitable for both buyers and sellers. Although e-commerce has spread throughout the world, there are still many Muslims who do not know the status of their online buying and selling transactions from the perspective of Islamic law. The approach method used in this research is normative juridical. The e-commerce transactions as a new business trend in this modern economic era, are not an economic activity that is prohibited by Islamic law. The conclusion, the benefit of consumers, it can be seen in Act No. 8 of 1999 concerning Consumer Protection by providing administrative sanctions against the seller/business actor if he commits certain actions that are not in accordance with the provisions stipulated in the Act